High-Quality Genome Assembly of Oleaginous Red Yeast Sporobolomyces roseus CGMCC 2.4355. (22nd November 2021) - Li, Chunji; Cheng, Ping; Sun, Yunhao; Qin, Di; Yu, Guohui
Abstract: Sporobolomyces roseus is an important oleaginous red yeast with critical biotechnological applications and has received significant recognition as a valuable source of industrial enzymes, carotenoids, and lipids. To reveal the genetic basis and functional components underlying its biotechnological applications, a high-quality genome assembly is required. Here, we present a novel genome assembly of S. roseus CGMCC 2.4355 using a combination of Illunima and Oxford Nanopore technologies. The genome has an assembly size of 21.4 Mb and consists of 15 scaffolds with an N50 length of 2, 126, 566 bp and GC content of 49.52%. The assembly is of high integrity, comprising 95.2% complete Benchmarking Universal Single-Copy Orthologs (BUSCOs) as evaluated by a genome completeness assessment. The genome was predicted to contain 8, 124 protein-coding genes, 6, 890 of which were functionally annotated. We believe that the combination of our analyses and high-quality genome assembly will promote the basic development of S. roseus as an agent for biotechnological applications and make a significant contribution to assess the evolutionary relationship of Sporobolomyces species.